An Attempt to Set Limits on Human Interference in the Environment - Latawiec, Michał (Studia Ecologiae et Bioethicae, 2016)
In this article the author discusses the problem of crossing the boundaries of human intervention in the environment that affect both nature and man. Setting limits on human interference in nature (and in man himself) is dependent on the type of the boundaries. For this reason, the author presents the issues of the role and development of human interference in nature, an attempt to justify the current intervention as well as the associated dilemmas. For the purpose of this analysis, the author formulates a definition of borderline interference in nature. Finally, the author gives examples of exceeding the permissible limits.